Effect of Organizational Engagement on Job Satisfaction of Employees of Bank for Agriculture and Agricultural Cooperatives, Mahasarakham Province - ปานศุภวัชร, อารีรัตน์; ปานศุภวัชร, ประวีณ (KKBS Journal of Business Administration and Accountancy, 2018)
This research examined the relationships and effects between organizational Engagement and job satisfaction of employee in Bank for Agriculture and Agricultural Cooperatives in Mahasarakham Province. A questionnaire was used as a tool for collecting the data from 180employee of Bank for Agriculture and Agricultural Cooperatives in Mahasarakham. The descriptive statisticsmultiple correlation and regression analysis were used to analyze the collected data. the results indicated that organizational Engagement consist of 3 dimensions, namely, Faith; Rules; andPromote had relationship and affect with job satisfaction. Moreover, the discussion with the outcomes was implemented in the study. In addition, managerial theoretical and contributions were described. Finally, conclusion, suggestions, and directions for the future research were presented.